Communication disorders in the correctional system: a systematic review - Iure de França; Larissa Monteiro; Bernardo Rodrigues; Ailton Melo (Sociedad Española de Sanidad Penitenciaria, 2023)
Abstract Objectives: Good communication is essential for resolving social conflicts, especially in closed communities such as prisons. When communication is interrupted by factors such as hearing loss or difficulties in coordination, voice, language, fluency, or disruption of any of the biological systems required to communicate, Human Communication Disorders can appear. This review aimed to identify the most prevalent communication disorders amongst prison inmates. Material and method: Systematic review through databases of studies that analyze individual inmates with communication disorders over the last 38 years. After reading the titles and abstracts and applying the eligibility criteria, 25 articles were selected and included in the final review. Results: A sample of 2,188 individuals was evaluated, two studies were conducted with a female population only, while twelve studied exclusively males, and 11 articles had a mixed population. All the studies included evaluated language and communication disorders in general, with language impairment being more prevalent There are no English language studies evaluating language and communication disorders in incarcerated individuals from African countries, Latin America or Asia. Discussion: Inmates have a high prevalence of language and communication disorders, and thus end up being more vulnerable within the prison system. Speech therapists are important members of the legal workforce and improve the health, well-being and participation of people in contact with or at risk of contact with the judicial system through the prevention, early detection, assessment and treatment of communication disorders.